2015
DOI: 10.1159/000431173
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intramuscular Injection of Autologous Immunoglobulin on Clinical Severity and Serum IgE Concentration in Patients with Atopic Dermatitis

Abstract: Background/Objective: The management of patients with atopic dermatitis (AD) is often difficult for both patients and physicians. We hypothesized that repeated intramuscular injections of autologous immunoglobulin can induce clinical improvement in patients with AD by correcting immune dysfunction. Methods: Seventeen adult patients with severe AD were treated by intramuscular injection of 50 mg autologous immunoglobulin (mainly IgG with a purity ≥97%) twice a week for 4 weeks. The standardized clinical severit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…This result suggested that immune dysfunction and hypersensitivity reaction play key roles in the pathogenesis of AD and could be the critical therapeutic targets for AD 3. Further development of a new therapeutic modality is required to change the long-term clinical course of AD 356…”
Section: Introductionmentioning
confidence: 99%
“…This result suggested that immune dysfunction and hypersensitivity reaction play key roles in the pathogenesis of AD and could be the critical therapeutic targets for AD 3. Further development of a new therapeutic modality is required to change the long-term clinical course of AD 356…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of atopic dermatitis with intramuscular immunoglobulin has been described in a pilot study of 17 adults . A regimen of 50 mg of autologous immunoglobulin twice weekly for 4 weeks was associated with a significant decrease in SCORAD and followed by remission for at least 8 weeks, with no evident side effects.…”
Section: Resultsmentioning
confidence: 99%
“…In 2015, the authors first demonstrated the efficacy of AIGT, which was a pilot study of 17 adult patients with severe AD. 5 In that study, AIGT given twice a week for 4 weeks significantly decreased clinical severity and serum immunoglobulin (Ig) E concentration in all 17 patients. In addition, clinical and laboratory improvements by AIGT lasted for 8 weeks even after its cessation.…”
mentioning
confidence: 75%